Identification of the CBF Gene Family in Wheat and TaCBF14B Could Enhance the Drought Tolerance of Arabidopsis thaliana - Zubaidai Abudukerimu; Yitu Xu; Shengjing Chen; Yuliu Tan; Caihong Li; Nan Niu; Yuxin Xie; Zihan He; Xiangyu Liu; Junwei Xin; Jiafei Yu; Junrong Li; et al. (Agronomy)
Drought stress is a devastating natural stress that threatens crop productivity and quality. Mitigating the adverse effects of drought stress on wheat is a key object in agriculture. C-repeat binding transcription factor/DROUGHT RESPONSE ELEMENT BINDING FACTOR 1 (CBF/DREB1) transcription factors are well known for their role in cold acclimation. However, the involvement of CBF genes in drought stress and the mechanisms underlying their function remain poorly understood. In this study, 81 CBFs were identified in wheat, which were further clustered into four distinct lineages based on phylogenetic analysis. Chromosomal localization indicated that most CBF genes were dispersed across chromosome 5. We identified three homoeologous genes (TaCBF14A, TaCBF14B, and TaCBF14D) that were simultaneously upregulated under drought stress based on RNA-seq analysis. According to the high expression after drought stress, TaCBF14B was selected for further functional analysis. Subcellular localization and transcriptional activation activity analysis indicated that TaCBF14B likely functions as a transcription factor involved in drought stress tolerance. Overexpression of TaCBF14B in Arabidopsis enhanced the primary root growth by 13.49% (OE1), 12.56% (OE2), and 19.53% (OE3) under 200 mM mannitol treatment, and 21.65% (OE1), 16.63% (OE2), and 28.13% (OE3) under 250 mM mannitol treatment compared to WT. Meanwhile, the water loss rate of transgenic lines was 56% in WT leaves, but only 44%, 50%, and 40% in OE1, OE2, and OE3 lines, respectively. Compared to the wild type, POD activities of OE1, OE2, and OE3 were significantly increased by 42.94%, 29.41%, and 62.52%, respectively. And the Pro activities in OE1, OE2, and OE3 were significantly increased by 16.33%, 5.18%, and 29.09%, respectively, compared to the wild type. Additionally, the MDA content in OE1, OE2, and OE3 was significantly reduced by 40.53%, 15.81%, and 54.36%, respectively. Further analysis showed that the transgenic lines were hypersensitive to abscisic acid (ABA), and exhibited increased expression of AtABI3. We speculate that TaCBF14B plays an important role in enhancing drought tolerance. In summary, our findings provide new insights into the functional roles of CBF genes in drought stress tolerance.